Strategi Pengembangan Potensi Wisata Desa Batur Tengah, Kintamani, Kabupaten Bangli, Bali - Damayanti, Ida Ayu Kade Werdika; Harisal, Harisal; Prayustika, Putu Adriani (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
This research has a very relevant objective, namely identifying the natural tourism potential that exists in Batur Tengah Village, especially in the context of the Kintamani area which is famous for its main destinations such as Lake Batur and Mount Batur. By identifying other tourism potentials that many tourists may not yet know about. Using the SWOT analysis technique (Strengths, Weaknesses, Opportunities, Threats) is a good approach for evaluating the potential for natural tourism in Central Batur Village. The data used by the author is in the form of qualitative data collected through direct observation and interviews. The data obtained in the field will be analyzed using qualitative descriptive analysis techniques by describing the situation in the field. In addition, there is also a need for a study of the potential and appropriate policies in realizing Batur Tengah Village into a tourist destination. Based on the results of the SWOT analysis, the tourism development strategy in Batur Tengah Village that may be implemented is as follows: environmental conservation, promotion of culture and traditions, training and education, infrastructure and accessibility, promotion of tourism, homestays and accommodation, sustainable tourism, economic sustainability, community participation, and evaluation and supervision. Keywords: Tourism Potential, Development, Strategy, SWOT. Abstrak Pengabdian ini memiliki tujuan yang sangat relevan, yaitu mengidentifikasi potensi wisata alam yang ada di Desa Batur Tengah, terutama dalam konteks kawasan Kintamani yang terkenal dengan destinasi utama seperti Danau Batur dan Gunung Batur. Dengan mengidentifikasi potensi wisata lain yang mungkin belum banyak dikenal oleh wisatawan. Penggunaan teknik analisis SWOT (Strengths, Weaknesses, Opportunities, Threats) adalah pendekatan yang baik untuk mengevaluasi potensi wisata alam di Desa Batur Tengah. Data yang diperoleh melalui observasi langsung dan wawancara adalah cara yang efektif untuk mendapatkan pemahaman yang mendalam tentang situasi saat ini dan perspektif masyarakat setempat. Data yang didapat di lapangan akan dianalisis menggunakan teknik analisis deskriptif kualitatif dengan menggambarkan situasi yang ada di lapangan. Selain itu, juga perlu adanya kajian mengenai potensi dan kebijakan yang sesuai dalam merealisasikan Desa Batur Tengah menjadi suatu destinasi wisata. Berdasarkan hasil analisis SWOT maka strategi pengembangan wisata Desa Batur Tengah yamg mungkin dapat diterapkan sebagai berikut : konservasi lingkungan, promosi budaya dan tradisi, pelatihan dan pendidikan, infrastruktur dan aksesbilitas, promosi wisata, homestay dan akomodasi, pariwisata berkelanjutan, keberlanjutan ekonomi, partisipasi masyarakat, serta evaluasi dan pengawasan. Kata Kunci: Potensi Wisata, Pengembangan, Strategi, SWOT .